2023
DOI: 10.1158/2159-8290.cd-22-0787
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Genomic Instability Prevents Acquired Resistance to MAPK Inhibitor Therapy in Melanoma

Abstract: Blocking cancer genomic instability may prevent tumor diversification and escape from therapies. We show that, after MAPK inhibitor (MAPKi) therapy in patients and patient-derived xenografts (PDXs), acquired-resistant genomes of metastatic cutaneous melanoma specifically amplify resistance-driver, non-homologous end-joining (NHEJ), and homologous recombination repair (HRR) genes via complex genomic rearrangements (CGRs) and extrachromosomal DNAs (ecDNAs). Almost all sensitive and acquired-resistant genomes har… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…If the FA pathway cannot be directly targeted even in short treatment intervals, targeting upstream kinases also offers promise. Clinical ATR, ATM, and DNA-PK inhibitors already exist for a variety of indications, and our work suggests that this class of kinases is at play in helping many types of MAPK-mutant escapee cells adapt and evolve amid cell-cycle stress and DNA damage, paralleling recent studies noting the effective cotreatment of MAPK inhibition with ATM inhibitors ( 76 ) or with DNA-PK inhibitors ( 77 ).…”
Section: Discussionsupporting
confidence: 64%
“…If the FA pathway cannot be directly targeted even in short treatment intervals, targeting upstream kinases also offers promise. Clinical ATR, ATM, and DNA-PK inhibitors already exist for a variety of indications, and our work suggests that this class of kinases is at play in helping many types of MAPK-mutant escapee cells adapt and evolve amid cell-cycle stress and DNA damage, paralleling recent studies noting the effective cotreatment of MAPK inhibition with ATM inhibitors ( 76 ) or with DNA-PK inhibitors ( 77 ).…”
Section: Discussionsupporting
confidence: 64%
“…Increased DSB persistence likely promotes ecDNA formation by (i) increasing the temporal overlap of the DSBs; (ii) enabling dissociation of the DSB ends from the their legitimate partners; and (iii) with increasing time, favoring the intramolecular ligation event ( Fig 4F ). Recent work has suggested that DNA-PKcs inhibition can decrease formation of ecDNA by chromothripsis, or decrease the genomic span of these ecDNAs (9,31). These seemingly diametric results may be a consequence of a greater reliance on NHEJ to ligate fragments generated by chromothripsis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although primary resistance is mainly linked to the initial tumor cell status and their microenvironment, to date there is still no biomarker to identify patients with BRAF V600 -mutated melanoma who will not respond to MAPKi. Acquired resistance involves the adaptation of tumor cells through genetic or non-genetic mechanisms [37, 38]. A single-cell study showed that tumor heterogeneity and melanoma cell plasticity influence tumor behavior and evolution under MAPKi pressure [39].…”
Section: Discussionmentioning
confidence: 99%